Sikap Orang Tua dengan Kejadian Obesitas pada Anak Usia 6-12 Tahun - Mochamad Heri; Komang Gde Trisna Purwantara; Ni Made Dwi Yunica Astriani; I Dewa Ayu Rismayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between parent's attitudes and the incidence of obesity in children aged 6-12 years at SD Negeri 1 Banyuasri. This type of research is descriptive correlational with a cross-sectional approach. This study indicates that 24 people (53.3%) have a positive attitude towards obesity in children aged 6-12 years with six (13.3%) obese children. Data analysis results with the Chi-Square test obtained a value of 0.000 or p<α (0.05). In conclusion, there is a significant relationship between parent's attitudes and the incidence of obesity in children aged 6-12 years at SD Negeri 1 Banyuasri. Keywords: Children 6-12 Years, Obesity, Parent’s Attitudes